In vivo assessment of the metabolic activity of CYP2D6 diplotypes and alleles. (2nd August 2015) - Hertz, Daniel L.; Snavely, Anna C.; McLeod, Howard L.; Walko, Christine M.; Ibrahim, Joseph G.; Anderson, Steven; Weck, Karen E.; Magrinat, Gustav; Olajide, Oludamilola; Moore, Susan; Raab, Rachel; Carrizosa, Daniel R.; et al.
Abstract : Aims: A prospectively enrolled patient cohort was used to assess whether the prediction of CYP2D6 phenotype activity from genotype data could be improved by reclassification of diplotypes or alleles. Methods: Three hundred and fifty‐five patients receiving tamoxifen 20 mg were genotyped for CYP2D6 and tamoxifen metabolite concentrations were measured. The endoxifen : N‐desmethly‐tamoxifen metabolic ratio, as a surrogate of CYP2D6 activity, was compared across four diplotypes ( EM/IM, EM/PM, IM/IM, IM/PM ) that are typically collapsed into an intermediate metabolizer (IM) phenotype. The relative metabolic activity of each allele type ( UM, EM, IM, and PM ) and each EM and IM allele was estimated for comparison with the activity scores typically assigned, 2, 1, 0.5 and 0, respectively. Results: Each of the four IM diplotypes have distinct CYP2D6 activity from each other and from the EM and PM phenotype groups (each P  < 0.05). Setting the activity of an EM allele at 1.0, the relative activities of a UM, IM and PM allele were 0.85, 0.67 and 0.52, respectively. The activity of the EM alleles were statistically different ( P  < 0.0001), with the CYP2D6* 2 allele (scaled activity = 0.63) closer in activity to an IM than an EM allele. The activity of the IM alleles were also statistically different ( P  = 0.014). Conclusion: The current systems for translating CYP2D6 genotype into phenotype are not optimally calibrated, particularly in regards to IM diplotypes and the *2 allele. Additional research is needed to improve the prediction of CYP2D6 activity from genetic data for individualized dosing of CYP2D6 dependent drugs.